2022
DOI: 10.3390/su14031048
|View full text |Cite
|
Sign up to set email alerts
|

African Case Studies: Developing Pavement Temperature Maps for Performance-Graded Asphalt Bitumen Selection

Abstract: The reliable performance of roads is crucial for service delivery, and it is a catalyst for domestic and cross-border spatial development. Paved national roads are expected to carry higher traffic volumes over time as a result of urbanization and to support the economic development in the continent. Increased traffic levels combined with expected increases in air temperatures as a result of global warming highlight the need to appropriately select bituminous road materials for a reliable performance of asphalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Some studies on Zhengzhou City found that green space and water can effectively reduce LST and mitigate the UHI effect [28,44]. Albedo decrease due to urbanization leads to LST increase [45][46][47]. These findings strongly confirm the plausibility of the above spatial heterogeneity of LST.…”
Section: Comparison With Previous Studiesmentioning
confidence: 64%
“…Some studies on Zhengzhou City found that green space and water can effectively reduce LST and mitigate the UHI effect [28,44]. Albedo decrease due to urbanization leads to LST increase [45][46][47]. These findings strongly confirm the plausibility of the above spatial heterogeneity of LST.…”
Section: Comparison With Previous Studiesmentioning
confidence: 64%
“…Sci. 2023, 13, 4164 2 of 12 Extensive research has been carried out across the world and in different climatological regions to formulate pavement temperature prediction models that can be used to select asphalt binder materials for asphalt roads [3,4]. The models can be categorised as theoretical-based on the principles of heat transfer-or empirical models-based on statistical analysis of the measured environmental factors to determine pavement temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Mokoena et al [12] pointed out that pavement temperature relies on more than air temperature-it is determined based on various climatic and weather factors as well as on pavement material properties and the overall pavement structure. Future studies should be performed for distinct types of bitumen used in flexible pavements, as the retention potential can vary with the bitumen type.…”
Section: Discussionmentioning
confidence: 99%
“…Austroroads [11] considered that the life of bituminous surface treatments will be affected by ambient temperature; the increase in temperature will accelerate the rate of deterioration of seal binders and require earlier surface dressings/reseals, which will lead to higher maintenance costs. Mokoena et al [12] show concern for the global warming and the need to appropriately decide on bituminous road materials for a reliable performance of asphalt roads in South Africa. Fletcher et al [13] used observations, output from global climate models, and a statistical model to evaluate the extreme maximum pavement temperature in 17 major Canadian cities, concluding that for most of the cases there will be a projected increased temperature.…”
Section: Introduction 1climate Change Impacts On Road Pavement and Ro...mentioning
confidence: 99%